2018
DOI: 10.1557/mrs.2018.154
|View full text |Cite
|
Sign up to set email alerts
|

Lead-free piezoelectrics—The environmental and regulatory issues

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
101
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(101 citation statements)
references
References 9 publications
0
101
0
Order By: Relevance
“…It is evident that there is a minimal temperature dependence for W r , while η decreases slightly at high temperatures but still retains values of η >80%. Figure compares the energy density W r and efficiency η at 175°C of the 110‐textured 10BSBT films with those of other materials . It can be observed that the 10BSBT films provide an optimum combination of W r and η at high temperatures and therefore are an attractive option for high‐energy‐storage capacitor applications that are intended for temperatures of 140°C and above.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…It is evident that there is a minimal temperature dependence for W r , while η decreases slightly at high temperatures but still retains values of η >80%. Figure compares the energy density W r and efficiency η at 175°C of the 110‐textured 10BSBT films with those of other materials . It can be observed that the 10BSBT films provide an optimum combination of W r and η at high temperatures and therefore are an attractive option for high‐energy‐storage capacitor applications that are intended for temperatures of 140°C and above.…”
Section: Resultsmentioning
confidence: 97%
“…WA and AP gratefully acknowledge funding support from City University of Hong Kong (Projects No. 7200514, F I G U R E 5 Comparison of recoverable energy storage density (W r ) and efficiency (η) of 110-textured 10BSBT films with respect to other Pb-based and Pb-free thin films 2,5,8,[30][31][32][33][34][35][36][37]…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since PZT ceramics contain about 60 wt% of toxic lead, their wide use leads to contamination during manufacture and disposal. The respective environmental concern has been discussed in detail recently . Thus, there is an urgent demand to develop lead‐free piezoceramics for actuator applications.…”
Section: Introductionmentioning
confidence: 99%
“…Exemption 7(c)-I, for example, has been recently reviewed and provides an exemption for lead in piezoelectronic devices until July 2021, with applications for further extension of this exemption due to the European commission by January 2020. Bell and Deubzer 6 have outlined current legislation and future options.…”
Section: Introductionmentioning
confidence: 99%